Aggregated neutrophil extracellular traps occlude Meibomian glands during ocular surface inflammation - Mahajan, Aparna; Hasíková, Lenka; Hampel, Ulrike; Grüneboom, Anika; Shan, Xiaomei; Herrmann, Irmgard; Garreis, Fabian; Bock, Felix; Knopf, Jasmin; Singh, Jeeshan; Mahajan, Siddharth; Leppkes, Moritz; et al. (Ocular Surface, 2021)
Purpose: Obstructive Meibomian gland dysfunction (MGD) is one of the leading causes of evaporative dry eye disease. Meibomian glands at the eyelid secrete lipids that prevent evaporation of the aqueous tear film. The pathogenesis of obstructive MGD is incompletely understood to date. Herein, we aim to investigate the pathogenesis of obstructive MGD using murine and human samples with various forms of ocular surface inflammation. Method: The presence of Neutrophil extracellular Traps (NETs) was detected with immunofluorescence analysis of ocular surface discharge and biopsy samples from patients with blepharitis. Tear fluid from patients with MGD and blepharitis were evaluated for the presence of inflammatory mediators using bead based immunoassay. Murine model of allergic eye disease (AED) was performed to investigate the role of NETs in MG occlusion. Results: we show that the ocular discharge from patients with blepharitis contains aggregated neutrophil extracellular traps (aggNETs). Furthermore, the ducts of human Meibomian glands affected by blepharitis were largely congested by aggNETs. Tear fluid from patients with MGD showed elevated neutrophil chemoattractants (C5a, IL6, IL8 and IL18). C5a and IL8 correlated with the degree of deficiency of tear fluid. In the murine model of allergic eye disease (AED), aggNETs accumulated in the MG leading to occlusion of their ducts and the retrograde pent-up of the fluid followed by acinar atrophy. Constraining aggNET formation by genetic or pharmacological inhibition of peptidyl arginine deiminase type 4 (PADI4) effectively reduced MG damage. Conclusion: We conclude that aggNETs occlude MG causing MGD after ocular surface inflammation.
CRIS-Team Scopus Importer:2021-01-15
Keywords: Blepharitis; Meibomian gland dysfunction (MGD); Neutrophil extracellular traps (NETs); Occlusion

A Pleomorphic Puzzle: Heterogeneous Pulmonary Vascular Occlusions in Patients with COVID-19 - Singh, Jeeshan; Herrmann, Irmgard; Mahajan, Aparna; Schauer, Christine; Shan, Xiaomei; Hartmann, Arndt; Rieker, Ralf; Evert, Katja; Falkeis, Christina; Naschberger, Elisabeth; von Stillfried, Saskia; Boor, Peter; et al. (International Journal of Molecular Sciences, 2022)
Vascular occlusions in patients with coronavirus diseases 2019 (COVID-19) have been frequently reported in severe outcomes mainly due to a dysregulation of neutrophils mediating neutrophil extracellular trap (NET) formation. Lung specimens from patients with COVID-19 have previously shown a dynamic morphology, categorized into three types of pleomorphic occurrence based on histological findings in this study. These vascular occlusions in lung specimens were also detected using native endogenous fluorescence or NEF in a label-free method. The three types of vascular occlusions exhibit morphology of DNA rich neutrophil elastase (NE) poor (type I), NE rich DNA poor (type II), and DNA and NE rich (type III) cohort of eleven patients with six males and five females. Age and gender have been presented in this study as influencing variables linking the occurrence of several occlusions with pleomorphic contents within a patient specimen and amongst them. This study reports the categorization of pleomorphic occlusions in patients with COVID-19 and the detection of these occlusions in a label-free method utilizing NEF.
CRIS-Team Scopus Importer:2022-12-23
Keywords: age; COVID-19; gender; immunothrombosis; native endogenous fluorescence; occlusions; pleomorphism; SARS-CoV-2

Early Histopathological Changes of the Salivary Glands Associated with the Development of Primary Sjogren's Syndrome - Shan, Xiaomei; Reichardt, Clara; Singh, Jeeshan; Zeitler, Anne; Schauer, Christine; Knopf, Jasmin; Herrmann, Martin; Grossmayer, Gerhard; Schett, Georg; Munoz, Luis Enrique (ARTHRITIS & RHEUMATOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-13

Graphene-Induced Hyperthermia (GIHT) Combined With Radiotherapy Fosters Immunogenic Cell Death - Podolska, Malgorzata; Shan, Xiaomei; Janko, Christina; Boukherroub, Rabah; Gaipl, Udo; Szunerits, Sabine; Frey, Benjamin; Munoz, Luis Enrique (Frontiers in Oncology, 2021)
Radiotherapy and chemotherapy are the standard interventions for cancer patients, although cancer cells often develop radio- and/or chemoresistance. Hyperthermia reduces tumor resistance and induces immune responses resulting in a better prognosis. We have previously described a method to induce tumor cell death by local hyperthermia employing pegylated reduced graphene oxide nanosheets and near infrared light (graphene-induced hyperthermia, GIHT). The spatiotemporal exposure/release of heat shock proteins (HSP), high group mobility box 1 protein (HMGB1), and adenosine triphosphate (ATP) are reported key inducers of immunogenic cell death (ICD). We hypothesize that GIHT decisively contributes to induce ICD in irradiated melanoma B16F10 cells, especially in combination with radiotherapy. Therefore, we investigated the immunogenicity of GIHT alone or in combination with radiotherapy in melanoma B16F10 cells. Tumor cell death in vitro revealed features of apoptosis that is progressing fast into secondary necrosis. Both HSP70 and HMGB1/DNA complexes were detected 18 hours post GIHT treatment, whereas the simultaneous release of ATP and HMGB1/DNA was observed only 24 hours post combined treatment. We further confirmed the adjuvant potential of these released DAMPs by immunization/challenge experiments. The inoculation of supernatants of cells exposed to sole GIHT resulted in tumor growth at the site of inoculation. The immunization with cells exposed to sole radiotherapy rather fostered the growth of secondary tumors in vivo. Contrarily, a discreet reduction of secondary tumor volumes was observed in mice immunized with a single dose of cells and supernatants treated with the combination of GIHT and irradiation. We propose the simultaneous release of several DAMPs as a potential mechanism fostering anti-tumor immunity against previously irradiated cancer cells.
CRIS-Team Scopus Importer:2021-09-17
Keywords: hyperthermia; immunogenic cell death; melanoma; multimodal; radiotherapy; reduced graphene oxide

Hypoxia Promotes Neutrophil Survival After Acute Myocardial Infarction - Dölling, Maximilian; Eckstein, Markus; Singh, Jeeshan; Schoen, Janina; Shan, Xiaomei; Bozec, Aline; Knopf, Jasmin; Schett, Georg; Munoz Becerra, Luis; Herrmann, Martin; Schauer, Christine (Frontiers in Immunology, 2022)
Phagocytosis, degranulation, and neutrophil extracellular traps (NETs) formation build the armory of neutrophils for the first line of defense against invading pathogens. All these processes are modulated by the microenvironment including tonicity, pH and oxygen levels. Here we investigated the neutrophil infiltration in cardiac tissue autopsy samples of patients with acute myocardial infarction (AMI) and compared these with tissues from patients with sepsis, endocarditis, dermal inflammation, abscesses and diseases with prominent neutrophil infiltration. We observed many neutrophils infiltrating the heart muscle after myocardial infarction. Most of these had viable morphology and only few showed signs of nuclear de-condensation, a hallmark of early NET formation. The abundance of NETs was the lowest in acute myocardial infarction when compared to other examined diseases. Since cardiac oxygen supply is abruptly abrogated in acute myocardial infarction, we hypothesized that the resulting tissue hypoxia increased the longevity of the neutrophils. Indeed, the viable cells showed increased nuclear hypoxia inducible factor-1α (HIF-1α) content, and only neutrophils with low HIF-1α started the process of NET formation (chromatin de-condensation and nuclear swelling). Prolonged neutrophil survival, increased oxidative burst and reduced NETs formation were reproduced under low oxygen tensions and by HIF-1α stabilization in vitro. We conclude that nuclear HIF-1α is associated with prolonged neutrophil survival and enhanced oxidative stress in hypoxic areas of AMI.
CRIS-Team Scopus Importer:2022-03-04
Keywords: acute myocardial infarction; DNA decondensation; hypoxia inducible factor 1; NET formation; neutrophil extracellular traps; neutrophils

Induction of Ocular Surface Inflammation and Collection of Involved Tissues - Singh, Jeeshan; Shan, Xiaomei; Mahajan, Aparna; Herrmann, Martin; Schauer, Christine; Knopf, Jasmin; Munoz Becerra, Luis (Journal of Visualized Experiments, 2022)
Ocular surface diseases include a range of disorders that disturb the functions and structures of the cornea, conjunctiva, and the associated ocular surface gland network. Meibomian glands (MG) secrete lipids that create a covering layer that prevents the evaporation of the aqueous part of the tear film. Neutrophils and extracellular DNA traps populate MG and the ocular surface in a mouse model of allergic eye disease. Aggregated neutrophil extracellular traps (aggNETs) formulate a mesh-like matrix composed of extracellular chromatin that occludes MG outlets and conditions MG dysfunction. Here, a method for inducing ocular surface inflammation and MG dysfunction is presented. The procedures for collecting organs related to the ocular surface, such as the cornea, conjunctiva, and eyelids, are described in detail. Using established techniques for processing each organ, the major morphological and histopathological features of MG dysfunction are also shown. Ocular exudates offer the opportunity to assess the inflammatory state of the ocular surface. These procedures enable the investigation of topical and systemic anti-inflammatory interventions at the preclinical level.
CRIS-Team Scopus Importer:2022-09-02

NEUTROPHILS AND NETS AS ORCHESTRATORS OF INFLAMMATORY DISEASES - Hosari, D.; Hosari, Sami; Mahajan, Aparna; Oreski, Leticija; Schoen, J.; Shan, Xiaomei; Singh, Jeeshan; Wang, H.; Yaykasli, Kürsat Oguz; Knopf, Jasmin; Munoz, Luis Enrique; Schauer, Christine; et al. (CLINICAL AND EXPERIMENTAL RHEUMATOLOGY, 2021)
CRIS-Team WoS Importer:2021-09-17